Sustainable refrigeration and HVAC systems with natural fluids: An energy efficiency case Study - Garcia, João; Semedo, Arian; Almeida, Bruno (International Journal of Innovative Research and Scientific Studies, 2025)
This study explores the integration of refrigeration and HVAC systems utilizing natural refrigerants, ammonia (NH3, R717) and propane (R290), aiming to improve energy efficiency and minimize environmental impact. A case study was conducted at a commercial facility in Luanda, Angola, where the original refrigeration system was replaced and integrated with the HVAC system. The proposed system showed significant performance improvements and compliance with F-GAS regulations. The Coefficient of Performance (COP) increased from 2.29 to 3.53 in summer and from 2.21 to 3.12 in winter, reflecting substantial energy efficiency gains. Annual energy consumption decreased by 548,225 kWh (33.8%), leading to a corresponding reduction in CO₂ emissions by 53,726 kg (33.8%). These reductions align with global climate commitments such as the Kyoto Protocol and the Paris Agreement, demonstrating the potential of integrated systems to mitigate climate change. The system exhibited strong adaptability to climatic conditions, with efficient operation at a COP of 3.53 in summer and 3.12 in winter. The integration of refrigeration and HVAC systems with natural refrigerants not only enhances energy efficiency and reduces CO₂ emissions but also provides long-term economic benefits through operational cost reductions. The study emphasizes the importance of system integration as a sustainable solution in the refrigeration and HVAC industries, contributing to the advancement of energy-efficient technologies and supporting global climate mitigation goals.